Mengenal Gaya Belajar sebagai Strategi Orangtua dalam Mendampingi Anak School From Home di Masa Pandemi Covid (Jurnal Bimbingan dan Konseling Islam, 2021)
This reserch aims to find strategies that can be used by parents to assist children in school from home through the introduction of children's learning styles. The method of this research was using library research . Data collection technique used in this research is documentation method. Data analysis technique used ini this research was content analysis. The results of this research which includes; Recognizing the characteristics of various learning styles, how to identify and learning strategies that parents can apply according to the child's learning style, and the benefits of learning in a way that suits the child's learning style.